IB MYP Mathematics 4 & 5 Standard - Rose Harrison (Oxford University Press Oxford, United Kingdom, 2016)
Build solid mathematical understanding and develop key conceptual connections. The inquiry-based approach integrates the MYP key concepts, helping you shift to a concept-based approach and cement mathematical comprehension. Fully comprehensive and matched to the Revised MYP to help you progress learners into DP Mathematics. Progress your learners into IB Diploma - fully comprehensive and matched to the Next Chapter curriculum Drive mathematical confidence - extensive practice refines and progresses skills and understanding Develop understanding and flexiblity - integrated global contexts equip learners to recognize and manipulate new principles Enable learners to confidently apply understanding as they progress - strengthening performance in the eAssessment and IB Diploma Support higher level thinking skills through an approach grounded in factual, conceptual and debatable questions Develop conceptual, integrated teaching in the best way for your learners - learn by mathematical unit or by key concept Develop meaningful cross-curricular connections that help learners recognize and manipulate mathematical ideas in other disciplines Fully matched to the Next Chapter curriculum and supports the Common Core
Keywords: MYP Mathematics + MYP Student Resource Mathematics -- MYP Mathematics + MYP Student Resource Mathematics